The Mediating Role of Students’ Digital Literacy in the Relationship Between Artificial Intelligence Based Learning Tools and Academic Performance - Ahmed, Rizwan (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
Artificial intelligence (AI) has become the inseparable part of the contemporary education that gives students adaptative and personalised learning experiences. Nevertheless, the effectiveness of AI-based learning tools in terms of academic performance can be predetermined by the skills of students to operate digital technologies. The purpose of this research was to examine how the mediating variable of digital literacy of the students influenced the relationship between the academic performance and AI-based learning tools. The cross-sectional correlational design was applied and a convenience sample of 243 university students enrolled in AI-supported courses located in Karachi, Pakistan. Three standardised measures were used, including AI-Based Learning Tools Utilisation Scale, Digital literacy competence Questionnaire, and Academic Performance Scale. To determine both direct and indirect effects, Pearson correlation coefficient and structural equation modelling (SEM) were used to analyse data. The results were meaningful positive correlations among AI-based learning tools and digital literacy (r = 0.462, P ≤ 0.01), digital literacy and academic performance (r = 0.418, P ≤ 0.01). The outcomes of the SEM showed that digital literacy was a strong mediator of the correlation between AI-based learning tools and academic performance ( 0.142, P < 0.001). The mediating effect of digital literacy among students, between the use of AI-based learning tools and academic performance, is quite notable. Boosting the digital literacy add more value to AI technologies and offer better learning results to students.